2004
DOI: 10.1111/j.1471-0528.2004.00132.x
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study for a randomised controlled trial of waterbirth versus land birth

Abstract: Objectives To assess the feasibility of undertaking an adequately powered multicentre study comparing waterbirth with land birth. To assess whether women are willing to participate in such a trial and whether participation has a negative effect on their birthing experience. Design A randomised controlled trial (RCT) with 'preference arm'.Setting District general hospital with 3600 deliveries annually.Population Women with no pregnancy complications and no anticipated problems for labour/delivery.Methods Women … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
187
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(190 citation statements)
references
References 17 publications
2
187
1
Order By: Relevance
“…The positive physiological effects of hydrotherapy can facilitate the neurohormonal interactions of labour, reducing pain, and potentially facilitates the progress of labour (11,12). Water immersion may be associated with improved uterine perfusion, less painful contractions and a shorter labour with fewer interventions (13)(14)(15) sion shortens the process of labour (1,15), however some others found no significant difference for the duration of the 1st stages of labour (13,(16)(17)(18)(19)(20). The present study also demonstrates that the 1st stage of labour is not shortened by immersion in water in either primigravidas or multigravidas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The positive physiological effects of hydrotherapy can facilitate the neurohormonal interactions of labour, reducing pain, and potentially facilitates the progress of labour (11,12). Water immersion may be associated with improved uterine perfusion, less painful contractions and a shorter labour with fewer interventions (13)(14)(15) sion shortens the process of labour (1,15), however some others found no significant difference for the duration of the 1st stages of labour (13,(16)(17)(18)(19)(20). The present study also demonstrates that the 1st stage of labour is not shortened by immersion in water in either primigravidas or multigravidas.…”
Section: Discussionmentioning
confidence: 99%
“…The present study also demonstrates that the 1st stage of labour is not shortened by immersion in water in either primigravidas or multigravidas. Cammu et al, Eckert et al, Rush et al and Woodward et al provided data on analgesia and anesthesia use in their studies and found that there was a significant reduction in the incidence of analgesia and anesthesia use among women placed in water during the first stage of labour (16,17,19,20). In the present study, we have shown that VAS scores indicating the pain felt by the women were lowest among women having water birth, even lower than the women labouring with epidural analgesia.…”
Section: Discussionmentioning
confidence: 99%
“…Childbirth is a personal and individual experience as well as a very vulnerable state of being for the birthing woman. A feasibility study regarding randomisation to either water birth or land-birth indicated that women were willing to participate (Woodward & Kelly, 2004). However it must be acknowledged that women willing to participate in intrapartal trials may differ from the birthing population in general.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…The water birth study found that the women were happy to participate to help produce evidence for healthcare professionals and other parents (Woodward & Kelly, 2004).…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…In 2004, Woodward et.al reported that from 1985 to 1999 a total of 150,000 births were performed underwater; however, no regional analyzis have been published as far as we know (Woodward & Kelly, 2004).…”
Section: Introductionmentioning
confidence: 99%